Emilio Sereni e la cartografia. Un incontro mancato? - Rossi, Luisa; Gemignani, Carlo A. (Ri-Vista. Research for landscape architecture, 2015)
The originality of Emilio Sereni’s new use of pictorial images in his most known work, have drawn the attention of many scholars. Regardless of positive or negative opinions, an underestimated evaluation of the countless types of sources used by the author for his argumentation about italian rural landscapes, has occurred. In particular, this work analyses the approach of Sereni towards historic and thematic cartography.